The Role of Dance Terminology in Linguistics (Eurasian Journal of Learning and Academic Teaching, 2023)
The article discusses the importance of dance as a form of artistic expression and communication. It emphasizes the role of the choreographer in creating dance routines, the importance of rhythm and timing in dance, and the visual impact of dancers' arrangements on stage. The article concludes by challenging assumptions about dance and arguing that it is a powerful tool of communication that embodies the human imagination, records our achievements, and distinguishes us as human beings.